Corporate social responsibility as corporate soft law: Mainstreaming ethical and responsible conduct in corporate governance - TAN, Eugene K. B. (Institutional Knowledge at Singapore Management University, 2013)
This article explores corporate social responsibility ("CSR') as a viable mode of regulation and governance in the corporate arena. A starting premise is that good corporate governance must move resolutely beyond a compliance mindset to one which recognises that effective corporate governance must have an ethical backbone in which the dimensions of responsibility, transparency, and accountability are evident, recognised and supported. Regulatory endeavours and corporate governance reforms in the past decade have increasingly intersected with mainstream CSR motivations. CSR is increasingly inducted and mainstreamed into corporate governance thinking, characterised by the dual perspective ofrisk management and values-driven/principled governance and operations. Ultimately, good governance must embrace and integrate values rather than just rules. As a standard setter, values-driven CSR recognises and urges companies to be mindful of their activities and impact on stakeholders and the wider operating environment. These impulses should be harnessed to complement and sharpen corporate governance.